2015
DOI: 10.1111/bjet.12352
|View full text |Cite
|
Sign up to set email alerts
|

Using mobile devices for learning in clinical settings: A mixed‐methods study of medical student, physician and patient perspectives

Abstract: This study was conducted with medical students, physicians, patients and carers in a paediatric and an adult hospital to determine use of mobile devices for learning, and beliefs and attitudes about others' use. Awareness of ethical, patient privacy and data security concerns was explored. The research was conducted using a mixed-methods sequential explanatory design through survey and focus groups for students and physicians, and a separate survey for patients and carers. Each arm of the study was analysed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
(63 reference statements)
0
29
0
3
Order By: Relevance
“…This research used a mixed‐methods sequential explanatory design (Ivankova, Creswell, & Stick, )—see (Scott et al, ). The research with students reported here involved a questionnaire collecting qualitative and quantitative data, followed by focus groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research used a mixed‐methods sequential explanatory design (Ivankova, Creswell, & Stick, )—see (Scott et al, ). The research with students reported here involved a questionnaire collecting qualitative and quantitative data, followed by focus groups.…”
Section: Methodsmentioning
confidence: 99%
“…It forms part of a larger study conducted in an adult and a paediatric hospital with students, physicians, patients and carers concerning use of mobile devices and attitude towards others' mobile device use. A paper published in this journal provided an overview of the entire study, with a focus on the comparisons between the participant groups (Scott, Nerminathan, Alexander, Phelps, & Harrison, ), and others outlined the specific research with patients and carers (Alexander, Nerminathan, Harrison, Phelps, & Scott, ) and physicians (Nerminathan, Harrison, Phelps, Alexander, & Scott, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mann et al (2015) found that 15/23 (65.2%) nursing students given an iPod Touch to use in patient care over 18 months felt that staff and patients assumed them guilty of nonwork use of the device, maybe because staff did not use mobile devices in patient care. Scott et al's (2015) focus groups of years 2 and 3 medical students suggested that they decided themselves whether to use a mobile device, despite the medical school prohibiting use and their own concerns about: etiquette; privacy and security; and patients wrongly assuming personal use. They were considerably more concerned than doctors about patients'/carers' reactions to student use (78.0% vs 32.7%, p < 0.0001).…”
Section: What Might Patients Think?mentioning
confidence: 99%
“…This is the aim of clinical placement and simulations, however critical analysis and linking theory to practice can be achieved through designing learning experiences around problem based learning and learner generated content and contexts, leading to the development of student critical analysis skills. Examples of authentic mobile clinical analysis projects in the literature include: Conradi et al (2009), Eysenbach (2008, Ming-Zher, Swenson, and Picard (2010), Scott, Nerminathan, Alexander, Phelps, and Harrison (2015), and Smordal and Gregory (2003). In the context of visual design education, todays' students need to develop capability as VR content creator experts as they prepare for a profession that increasingly moves beyond print-based media to enhanced user interactivity and immersion (Sinfield, 2013).…”
Section: Foundational Learning Theoriesmentioning
confidence: 99%